2022
DOI: 10.3889/oamjms.2022.7094
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Coleus Amboinicus Consumption Interventions in Increasing Breast Milk Production and Improving Maternal Health Status During COVID 19 Pandemic

Abstract: Insufficient milk production is a major problem for mothers who have just given birth and affects the health condition of postpartum mothers. One of the actions that can be taken to increase milk production and improve the health of postpartum mothers is to consume foods that can increase breast milk production, namely ingredients that contain galactagogue substances. Several types of herbal plants that are often consumed by postpartum mothers after giving birth to increase breast milk in North Sumatra, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…prolactin, to start producing breast milk prolactin produced by the pituitary gland stimulates the milk glands in the mother's breast (Asih, 2016) The effectiveness of giving the extract of the leaves of Bangun-bangun (coleus amboinicus lour) to postpartum mothers who experienced smooth milk production as many as 23 respondents while 7 respondents did not experience smooth breastfeeding. This is in line with (Nasution and Eliana, 2022) which states that Bangun-bangun leaves are effective in increasing breast milk production in postpartum mothers. 7 respondents who did not experience smooth breastfeeding were due to anxiety about the time before delivery so that their milk did not come out because the mother had thoughts of her breast milk not coming out and anxiety because she would face the delivery process.…”
Section: Smooth Milk Production After Being Given the Extract Of The ...supporting
confidence: 89%
“…prolactin, to start producing breast milk prolactin produced by the pituitary gland stimulates the milk glands in the mother's breast (Asih, 2016) The effectiveness of giving the extract of the leaves of Bangun-bangun (coleus amboinicus lour) to postpartum mothers who experienced smooth milk production as many as 23 respondents while 7 respondents did not experience smooth breastfeeding. This is in line with (Nasution and Eliana, 2022) which states that Bangun-bangun leaves are effective in increasing breast milk production in postpartum mothers. 7 respondents who did not experience smooth breastfeeding were due to anxiety about the time before delivery so that their milk did not come out because the mother had thoughts of her breast milk not coming out and anxiety because she would face the delivery process.…”
Section: Smooth Milk Production After Being Given the Extract Of The ...supporting
confidence: 89%
“…A study by Nasution in 2022 demonstrated that torbangun leaf soup supplementation increased the consumption of micro-nutrients among research subjects, surpassing the recommended dietary intake (RDI). This study showed that torbangun leaf soup could improve the micro-nutrient status of breastfeeding mothers (Nasution et al, 2022). A similar study conducted by Lutfiani in 2023 proved that torbangun leaves could increase breast milk production by up to 34.8% (Lutfiani & Nasrulloh, 2023).…”
Section: Effectiveness Of Torbangun Leaf Herbal Tea On the Duration O...supporting
confidence: 69%
“…In article A2, it is mentioned that the efficacy of giving Indian borage leaves (Coleus amboinicus lour) on a mother's milk secretion can be known by giving as much as 100 grams of Coleus amboinicus lour leaves with a frequency once a day for one week for postpartum mothers (Nasution et al, 2022). According to article A3, it was reported that the supplementation of Coleus amboinicus lour tea significantly raised prolactin levels (with a significance value of 0.014, p<0.05) and enhanced milk production (significance value of 0.046, p<0.05).…”
Section: Coleus Amboinicus Lourmentioning
confidence: 99%